A new GPC/TREF/LinELSD instrument to determine the molecular weight distribution and chemical composition: application to recycled polymers. Issue 8 (17th November 2021) - Boborodea, Adrian; O'Donohue, Stephen; Brookes, Alan
Abstract: The linearized evaporative light scattering detector (LinELSD) incorporates an inverse power function facilitating the characterization of polymers in solution. To show the benefits of the LinELSD, a versatile liquid chromatograph was built by combining a high temperature gel permeation chromatograph (HT-GPC), a fast cooling/heating oven of a gas chromatograph (GC), and the LinELSD. Apart from the main GPC functionality to measure the molecular weight distribution (MWD) of polymers, the injected samples can also be eluted as a function of polymer type by applying a temperature rising elution fractionation (TREF) program on the column placed in the GC oven. The hybrid GPC/TREF/LinELSD instrument removes the limitations of the commercial GPC and TREF systems manufactured with differential refractive index (DRI) or infrared (IR) detectors, which require a sensible difference between the refractive indices of polymer and solvent, or the absence of CH2 and CH3 groups in the solvent. Thus, the new instrument qualifies to characterize the chemical structure of recycled polymers, demanding more flexible analytical conditions than those previously developed for the virgin resin analysis. Moreover, the hybrid instrument allows to investigate polyolefin solutions in xylene and toluene, which are the preferred solvents for the selective extraction of high-performance polymers from mixed plastic waste, thus qualifying as a unique analytical solution to assess the emergent solvent-based purification industrial processes.